The Effects of Fibroblast and Macrophage Separated and Co-Culture Conditioned Medium on Sperm Parameters Disorders Induced by Testicular Torsion-Detorsion in Adult Rats - Mansooreh Mansooreh Mirzaei; Rasoul Shahrooz; Ali Shalizar Jalali; Farshid Sarrafzadeh-Rezaei; Nariman Mosaffa (Fasa University of Medical Sciences, 2019)
Background & Objective: Ischemia and Reperfusion (I/R) lead to the production of excessive reactive oxygen species (ROS). In the present study the protective effects of the cell culture conditioned medium (CM) on sperm quality disorder induced by torsion-detorsion (T-D) in adult rat's testis was evaluated. Materials & methods: In this study 42 adult rats were divided into seven groups. 1- Normal control group treated without surgery. 2- Laparotomy group, surgery operated without T-D. 3- T-D group, surgery operated along with T-D. 4- T-D+DMEM group, after T-D Dulbecco's Modified Eagle's Medium (DMEM) has been injected. 5-7 groups included T-D+F, T-D+M, and T-D+FM, along with T-D injected conditioned medium of fibroblast, macrophage, and fibroblast-macrophage co-culture respectively. All injections were made at a rate of 10μL once after T-D in the rete testis. After 35 days, sperm quality parameters were evaluated and obtained data were compared between groups by one-way ANOVA statistic method and Tukey test post hoc in P<0.05 level. Results: The experimental groups that received CM of the fibroblast and macrophage compared to groups T-D and T-D+DMEM there were showed ameliorative effects in comparison to T-D and T-D+DMEM groups. There was not observed any ameliorative effects in the T-D+FM group. Conclusion: The results of this study showed the high ability of supernatant of the separate fibroblast and macrophage culture and in improving sperm parameters after testicular T-D.